(untitled) (Indonesian Journal of Cultural and Community Development, 2024)
General background effective village financial management is crucial in Indonesia, especially in light of increasing government regulations aimed at improving transparency and accountability. Specific background this study focuses on the implementation of Minister of Home Affairs Regulation No. 20 of 2018, which outlines mandatory processes for village financial management. Knowledge gap despite the existence of this regulation, there is a lack of comprehensive understanding regarding its practical application across different villages. Aims this research to investigate the planning, implementation, administration, reporting, and accountability of village funds in accordance with the regulation. Results findings reveal that the village’s financial management processes comply with the regulation, demonstrating adherence to the required stages of management. Novelty the study provides a unique contribution by offering an in-depth analysis of village fund management within the context of regulatory compliance, highlighting both challenges and best practices. Implications the results emphasize the need for continued training and resources for village officials to ensure adherence to regulations and improve the effectiveness of village financial management systems. Highlights: • Compliance with Minister of Home Affairs Regulation No. 20 of 2018 is essential for effective fund management. • Involvement of the community in the planning process fosters transparency and accountability. • Comprehensive training for village officials is necessary to enhance financial management practices. Keywords: Finance, Village, Participation, Planning, Transparency